Ambient air pollution and lung cancer risk among never-smokers in the Women's Health Initiative. Issue 6 (December 2019) - Gowda, Shilpa N.; DeRoos, Anneclaire J.; Hunt, Rebecca P.; Gassett, Amanda J.; Mirabelli, Maria C.; Bird, Chloe E.; Margolis, Helene G.; Lane, Dorothy; Bonner, Matthew R.; Anderson, Garnet; Whitsel, Eric A.; Kaufman, Joel D.; et al.
Abstract : Background: Ambient air pollution is classified as a human carcinogen by the International Agency for Research on Cancer (IARC). However, epidemiologic studies supporting this classification have focused on lung cancer mortality rather than incidence, and spatial and temporal resolutions of exposure estimates have varied considerably across studies. Methods: We evaluated the association of outdoor air pollution and lung cancer incidence among never-smoking participants of the Women's Health Initiative (WHI) study, a large, US-based cohort of postmenopausal women (N = 65, 419; 265 cases). We used geospatial models to estimate exposures to fine particulate matter (PM2.5 ) and nitrogen dioxide (NO2 ) based on residential addresses at baseline and throughout follow-up. We also characterized exposures to traffic-related air pollution by proximity to major roadways. We estimated hazard ratios (HRs) for the risk of lung cancer in association with these exposure metrics using Cox proportional hazards regression models. Results: No compelling associations of PM2.5 and NO2 exposures with lung cancer risk were observed. An increased risk of lung cancer was observed when comparing those individuals with residences <50 versus ≥200 meters from a primary limited access highway (HR = 5.23; 95% confidence interval = 1.94, 14.13). Conclusions: Our results do not exclude lung cancer risk estimates observed in association with PM2.5 and NO2 exposures identified in previous studies. Our results suggest that residential proximity to major roadways may be a proxy for carcinogenic exposures not correlated with PM2.5 or NO2 levels. New studies of air pollution and lung cancer incidence should characterize additional aspects of proximity to major roadways.